Using digital differentiation to improve EFL achievement and self-regulation of tertiary learners: the Turkish context. Issue 2 (15th March 2023) - Meşe, Esra; Mede, Enisa
ABSTRACT: Purpose: The current study examines the impact of Differentiated Instruction (DI) on students' EFL speaking proficiency and Self-Regulated Learning (SRL) during online learning at a Turkish higher education institution's English preparatory program. Design/methodology/approach: Carried out as a sequential explanatory mixed-methods approach, this quasi-experimental study first collected quantitative data from two intact classrooms, experimental group ( n  = 16), control group ( n  = 15), through a speaking proficiency test and the Turkish translation of a Likert-type Online Self-Regulation Questionnaire (OSRLQ) as pre-/post-test; and qualitative data through a semi-structured focus group interview with six students. The qualitative data were coded and interpreted through content analysis. Findings: Based on Tomlinson's (2001) DI framework, the intervention plan of this study involved differentiating the process, product and learning environment of the online learners based on their readiness levels and interests. The results revealed that the DI-group improved its speaking significantly higher than the non-DI group whereas the overall SRL of the both groups did not differ meaningfully. The DI-group improved its help-seeking strategy use significantly. The analysis of qualitative data indicated that the students held positive views of online practices used for DI purposes such as formative assessment, differentiated speaking tasks while questioning group work arrangements. The participants also stated that they improved their use of target setting, help seeking and self-assessment. Originality/value: This study contributes to the literature in providing insight into the effects of differentiation practices during online learning and suggests implications for designing innovative differentiated EFL learning experiences during remote learning.